Penerapan Metode Qiraah Jahriyah untuk meningkatkan kemampuan membaca di Perguruan Tinggi - Hamdy, Mohammad Zainal; Umniyah, Umniyah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Reading is one of the language skills that must be mastered by students after listening and speaking skills. Because it is a difficult skill, teachers need appropriate methods and strategies so that students can absorb what is conveyed well. This study aims to apply the steps of the Qiraah Jahriyah Method to improve reading skills in Higher Education. Researchers use an interpretive paradigm with a qualitative approach and a field case study method, data generated through interviews and observations are analyzed with comprehensive data analysis. The results show that the steps of the Qiraah Jahriyah Method to improve reading skills in Higher Education include planning, preparation, implementation and evaluation which enable female students to increase their courage and reading skills effectively